Uji Sifat Fisik dan Palatabilitas Biskuit Limbah Tanaman Jagung sebagai Substitusi Sumber Serat untuk Domba (The Physical Characteristic and Palatability of Corn Plant Waste Biscuit as Fiber Substitution for Sheep) - Yuli Retnani; Lidy Herawati; Weny Widiarti; Eka Indahwati (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
Corn plant waste is one of alternative feed source that has big potential to make various low cost and useful feed product. One of technologies that can be applied to make feed biscuit is pressing technology. Biscuit feed is made byheating and pressing of forage usually it to become, thin, and flat. The objectives of this experiment were to determine physical characteristics and palatability of corn plant waste in the biscuit form for fiber substitution. The experimentaldesign used was Completely Randomized Design with 6 treatments and 3 replications. The treatment were : R1 (100% field grass), R2 (50% field grass+50% corn leaf), R3 (100% corn leaf), R4 (50% field grass+50% corn husk), R5 (50% corn leaf+50% corn husk) and R6 (100% corn husk). The data were subjected to ANOVA and Contrast Orthogonal Test. The observed variables were water activity, moisture, water absorption, density, and palatability. The results indicated that the treatments had highly significant effect (P<0.01) on water content. The water content of biscuits in R2 (11.06±0.10), R1 (11.23±0.60), and R6 (11.39±0.71) were lower than in biscuits R4 (11.73±0.17), R5 (11.80±0.09,) and R3 (12.85±0.37). The average of water content of all treatments was 11.68±0.34%. The treatments also significantly affected (P<0.05) water absorption of biscuit feed in which water absorption on R4 (514.48±19.95), R5 (504.27±5.59) and R1 (492.34±40.90) were higher than R6 (452.31±42.63), R3 (438.00±15.69) and R2 (383.49±31.97) with overall averages of 464.15±26.12%. Water activity, density, and palatability were not significantly different. It could be concluded that palatability of corn plant waste biscuit was the same with field grass biscuit on sheep.(Key words: Biscuit of corn plant waste, Physical characteristic, Palatability, Sheep)